2017
DOI: 10.1371/journal.pone.0175226
|View full text |Cite
|
Sign up to set email alerts
|

Vowel reduction in word-final position by early and late Spanish-English bilinguals

Abstract: Vowel reduction is a prominent feature of American English, as well as other stress-timed languages. As a phonological process, vowel reduction neutralizes multiple vowel quality contrasts in unstressed syllables. For bilinguals whose native language is not characterized by large spectral and durational differences between tonic and atonic vowels, systematically reducing unstressed vowels to the central vowel space can be problematic. Failure to maintain this pattern of stressed-unstressed syllables in America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
3
12
0
Order By: Relevance
“…Perhaps the failure of these intermediate L2 learners to shorten unstressed Spanish vowels as much as unstressed English ones could be attributed to their having already acquired the L2 durational features, even though their spectral features were not native-like. A similar finding is reported by Byers and Yavas (2017) for the acquisition of English /ə/ by early and late Spanish L1, English L2 bilinguals, although the early bilinguals were more native-like than the late bilinguals. They state that their findings suggest that "temporal properties of a language are better integrated into second language phonologies than spectral qualities" (p. 1), and our results provide independent support for this view.…”
Section: Durationsupporting
confidence: 87%
“…Perhaps the failure of these intermediate L2 learners to shorten unstressed Spanish vowels as much as unstressed English ones could be attributed to their having already acquired the L2 durational features, even though their spectral features were not native-like. A similar finding is reported by Byers and Yavas (2017) for the acquisition of English /ə/ by early and late Spanish L1, English L2 bilinguals, although the early bilinguals were more native-like than the late bilinguals. They state that their findings suggest that "temporal properties of a language are better integrated into second language phonologies than spectral qualities" (p. 1), and our results provide independent support for this view.…”
Section: Durationsupporting
confidence: 87%
“…Reduced vowels are produced with shorter duration than their full vowel counterparts. English makes frequent use of vowel reduction, thus creating variation in syllable length, but recent studies by Byers and Yavas (2016, 2017) have demonstrated that this phenomenon does not occur in Spanish. This can be interpreted as yet another phenomenon that yields greater variation in syllable duration in English compared to Spanish.…”
Section: Possible Polysyllabic Shortening In Spanishmentioning
confidence: 99%
“…In previous studies, acoustic characteristics of vowel reduction are concerned [7][8][9][10][11]. However, few studies have contributed to the area of automatically detecting vowel reduction.…”
Section: Introductionmentioning
confidence: 99%